Pengaruh Kecerdasan Spiritual Terhadap Pengelolaan Keuangan Pribadi - Peter Garlans Sina; Andris Noya (Universitas Kristen Maranatha, 2012)
Personal financial management latterly can't be ignored as time previous, because influence achievement personal’s welfare. This research is aimed to know spiritual's intelligence influence to personal financial management. The sample ofthis research was the psychology graduate students of Satya Wacana Christian University of Salatiga. Data were acquired by distributing the questioners. The result of the study showed that spiritual's intelligence having for positive but notsignificant to personal financial management.